Exploring Students"™ Smartphone Habits in A Project-Based Online Speaking Class - Rohmah, Farida Noor; Albanna, Dzar (Journal of English Education Program, 2024)
This study aims to analyze the students"™ smartphones usage in a project-based learning speaking online class. It has become essential to inquire into how smartphones are affecting academic activities given their increasing use and integration into daily life. This descriptive qualitative research was conducted to a class engaged in an English-speaking project at one of the private universities in Yogyakarta with semi-structured interview and document analysis technique. The findings highlight that smartphone were utilized by the students for accessing language learning resources, accessing online dictionary, participating in classroom activities, facilitating students"™ communication and interaction, and content creation. However, certain disadvantage was also found, namely the possibility of becoming dependent on the smartphone. The study's conclusions highlight the significance of supporting appropriate and intentional integration of smartphones into educational settings to maximize the positive effects while minimizing any potential negative effects.